Esponjas (Porifera, Demospongiae) indicadoras ambientais na APA Meandros do Rio Araguaia, Brasil - Batista, Twiggy Cristina Alves (2007)
A first survey for freshwater sponges was carried out at the protected Amazonian area of Meandros do Rio Araguaia , at the Brazilian states of Tocantins, Mato Grosso and Goiás. The survey aimed to sample the largest number of different freshwater habitats from this Amazonian clear waters area. It was carried out at different GPS registered sampling stations, during high and low water periods. Water and sediments were also sampled at the same time aiming to relate sponge occurrences with the measured habitat parameters. For that purpose, Canonical Correspondence Analysis (CCA) and Non-metric Multidimensional Scaling (MDS) analysis were carried out over 12 habitat variables. The taxonomic analysis yielded the detection of the occurrence in this area of 21 freshwater sponge species, with the description of Heteromeyenia cristalina n. sp and the revision of the genus Heteromeyenia Potts, 1881, for South America. Heteromeyenia cristalina, Trochospongilla gregaria, T. paulula, T. minuta, T. lanzamirandai, T. delicata, T. variabilis, T. pennsylvanica, Radiospongilla amazonensis, Saturnospongilla carvalhoi, Acalle recurvata and Drulia browni indicated the seasonally flooded ponds and forest, Spongilla spoliata, Trochospongilla repens, Oncosclera navicella, O. spinifera and Drulia ctenosclera, indicated the rocky bottoms dwellers, Corvospongilla seckti and Oncosclera navicella were common to both habitats. Dissolved oxygen concentration, pH, and organic matter were the variables which indicated species higher richness at the different habitats. The high water variables appeared as the most important ones, since they favor sponges distribution and production in this area.